Fibrinogen-albumin ratio predicts treatment response in phospholipase A2 receptor-associated membranous nephropathy with nephrotic syndrome - Suyan Duan; Si Chen; Chen Chen; Fang Lu; Ying Pan; Yifei Lu; Qing Li; Simeng Liu; Bo Zhang; Huijuan Mao; Changying Xing; Yanggang Yuan (Renal Failure)
Background The M-type phospholipase A2 receptor (PLA2R)-associated primary membranous nephropathy (PMN) is an immune-related disease in adults with increasing morbidity and variable treatment response, in which inflammation may contribute to the multifactorial immunopathogenesis. The relationship between fibrinogen-albumin ratio (FAR), serving as a novel inflammatory biomarker, and PMN is still unclear. Therefore, this study aims to clarify the association between FAR and disease activity and therapy response of PMN.Methods 110 biopsy-proven phospholipase A2 receptor (PLA2R) -associated PMN participants with nephrotic syndrome from January 2017 to December 2021 were recruited in the First Affiliated Hospital of Nanjing Medical University. The independent risk factors of non-remission (NR) and the predictive ability of FAR were explored by Cox regression and receiver-operating characteristic (ROC) curve analysis. According to the optimal cutoff value, study patients were categorized into the low-FAR group (≤the cutoff value) and the high-FAR group (>the cutoff value). Spearman’s correlations were used to examine the associations between FAR and baseline clinicopathological characteristics. Kaplan-Meier method was used to assess the effects of FAR on remission.Results In the entire study cohort, 78 (70.9%) patients reached complete or partial remission (CR or PR). The optimal cutoff value of FAR for predicting the remission outcome (CR + PR) was 0.233. The Kaplan-Meier survival analysis demonstrated that the high-FAR group (>0.233) had a significantly lower probability to achieve CR or PR compared to the low-FAR group (≤0.233) (Log Rank test, p = 0.021). Higher levels of FAR were identified as an independent risk factor for NR, and the high-FAR group was associated with a 2.27 times higher likelihood of NR than the low-FAR group (HR 2.27, 95% CI 1.01, 5.13, p = 0.048). These relationships remained robust with further analysis among calcineurin inhibitors (CNIs)-receivers. In the multivariate Cox regression model, the incidence of NR was 4.00 times higher in the high-FAR group than in the low-FAR group (HR 4.00, 95% CI 1.41, 11.31, p = 0.009). Moreover, ROC analysis revealed the predictive value of FAR for CR or PR with a 0.738 area under curve (AUC), and the AUC of anti-PLA2R Ab was 0.675. When combining FAR and anti-PLA2R Ab, the AUC was boosted to 0.766.Conclusions FAR was significantly correlated with proteinuria and anti-PLA2R Ab in PMN. As an independent risk factor for NR, FAR might serve as a potential inflammation-based prognostic tool for identifying cases with poor treatment response, and the best predictive cutoff value for outcomes was 0.233.